Differentiated instruction for mathematical problem-solving ability: A study on kinesthetic learners in probability - Pertiwi, Amirah Nada; Susanti, Ely (Universitas Maritim Raja Ali Haji, 2026)
Mathematical problem-solving ability is essential in mathematics learning. This study aims to describe the mathematical problem-solving ability of ninth-grade students in class IX.E at SMP Negeri 1 Indralaya on the topic of probability through the implementation of differentiated learning tailored to kinesthetic learning styles. This research is a descriptive study involving 20 students who tend to have a kinesthetic learning style, identified through a learning style questionnaire. The learning process was designed to include physical activities, hands-on experiments, and group work to match the characteristics of kinesthetic learners. Data were collected through a mathematical problem-solving test developed from problem-solving indicators, supplemented by observations and interviews. The results showed that students' mathematical problem-solving abilities learning were categorized as high (25%), medium (30%), and low (45%) where kinesthetic learners were categorized as low. Students experienced difficulties in several indicators of problem-solving, particularly in understanding problems, planning solution strategies, implementing problem-solving steps, and rechecking the results. Most errors occurred because students were not accustomed to identifying important information, connecting information to formulate solution plans, and evaluating the correctness of their answers. These findings indicate that kinesthetic learners still need more support and practice to develop systematic and reflective problem-solving skills in learning probability.